2020
DOI: 10.3390/pharmaceutics12100934
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning N-Acetylcysteine (NAC): NAC-Loaded Electrospun Drug Delivery Scaffolding for Potential Neural Tissue Engineering Application

Abstract: Traumatic brain injury (TBI) presents a serious challenge for modern medicine due to the poor regenerative capabilities of the brain, complex pathophysiology, and lack of effective treatment for TBI to date. Tissue-engineered scaffolds have shown some experimental success in vivo; unfortunately, none have yielded consummate results of clinical efficacy. N-acetylcysteine has shown neuroprotective potential. To this end, we developed a N-acetylcysteine (NAC)-loaded poly(lactic-co-glycolic acid) (PLGA) electrospu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
(75 reference statements)
3
10
0
Order By: Relevance
“…The fibers produced by 5% PCL solution are narrower than those produced by 10% PCL solution. It has been well reported that the nanofibers produced by electrospinning enlarge with the increase of polymer concentration used for synthesis [ 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibers produced by 5% PCL solution are narrower than those produced by 10% PCL solution. It has been well reported that the nanofibers produced by electrospinning enlarge with the increase of polymer concentration used for synthesis [ 11 , 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the thickness, hydrophobicity and molecular interaction of fibers and transporting molecules can be a tool to impact release, would the fiber diameter and pore size be another tool to manipulate the release? It has been well reported that the fiber diameter produced by electrospinning can be reduced by decreasing the polymer concentration used for synthesis process [ 11 , 12 , 13 ]. It was also reported in microfiltration that the flux of molecules can be altered by changing the microstructure of the nanofiber membranes such as the fiber diameter and porosity [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the broadening peak of the PLGA polymer and disappearance of melting peaks instead of the intense sharp peak of the drug in the NAC-PLGA-MPPs further scrutinized that NAC was integrated into the polymer matrix; thus exists in the amorphous or partially crystalline state ( Fig. 3 D) ( Mahumane et al., 2020 ). This study also iterates the presence of the drug in a solubilized state in the lipid due to solid-state interaction induced by heating as mentioned in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Drug-loaded electrospun neural conduits also hold great attention (Mahumane et al 2020;Haidar et al 2021;Farzamfar et al 2018). In this concept, a gabapentinloaded cellulose acetate/gelatin wet-electrospun scaffold was fabricated for neural tissue regeneration (Farzamfar et al 2018).…”
Section: Nerve Tissue Engineering Scaffoldsmentioning
confidence: 99%
“…Improved regeneration of the created injury was achieved with the drug-loaded scaffold when compared with the gabapentin-free scaffold. N-acetylcysteine-incorporated PLGA biomimetic neuro-scaffold for traumatic brain injury was also found to be neurocompatible through ex vivo cytotoxicity assays that were realized on rat pheochromocytoma (PC12) and human glioblastoma multiform (A172) cell lines with a positive influence on cell proliferation (Mahumane et al 2020). In another study, the combined multi-technologies were used to determine the neuroprotective effects of atorvastatin and alpha-lipoic acid as active pharmaceutical ingredients in a composite scaffold.…”
Section: Nerve Tissue Engineering Scaffoldsmentioning
confidence: 99%